Protecting the healthcare workforce during COVID-19: a qualitative needs assessment of employee occupational health in the US national Veterans Health Administration - Cati Brown-Johnson; Karl A Lorenz; Sara J Singer; Matthew D McCaa; Susan Giannitrapani; Elizabeth M Yano; Wendy T Thanassi; Cheyenne DeShields; Karleen F Giannitrapani (BMJ Open, 2021)
Objective Early in the COVID-19 pandemic, US Veterans Health Administration (VHA) employee occupational health (EOH) providers were tasked with assuming a central role in coordinating employee COVID-19 screening and clearance for duty, representing entirely novel EOH responsibilities. In a rapid qualitative needs assessment, we aimed to identify learnings from the field to support the vastly expanding role of EOH providers in a national healthcare system.Methods We employed rapid qualitative analysis of key informant interviews in a maximal variation sample on the parameters of job type, rural versus urban and provider gender. We interviewed 21 VHA EOH providers between July and December 2020. This sample represents 15 facilities from diverse regions of the USA (large, medium and small facilities in the Mid-Atlantic; medium sites in the South; large facilities in the West and Pacific Northwest).Results Five interdependent needs included: (1) infrastructure to support employee population management, including tools that facilitate infection control measures such as contact tracing (eg, employee-facing electronic health records and coordinated databases); (2) mechanisms for information sharing across settings (eg, VHA listserv), especially for changing policy and protocols; (3) sufficiently resourced staffing using detailing to align EOH needs with human resource capital; (4) connected and resourced local and national leaders; and (5) strategies to support healthcare worker mental health.Our identified facilitators for EOH assuming new challenging and dynamically changing roles during COVID-19 included: (A) training or access to expertise; (B) existing mechanisms for information sharing; (C) flexible and responsive staffing; and (D) leveraging other institutional expertise not previously affiliated with EOH (eg, chaplains to support bereavement).Conclusions Our needs assessment highlights local and system level barriers and facilitators of EOH assuming expanded roles during COVID-19. Integrating changes both within and across systems and with alignment of human capital will enable EOH preparedness for future challenges.